Analisis Aksesibilitas Perpustakaan bagi Difabel Berdasarkan pada Standar IFLA di Dinas Perpustakaan Propinsi Sumatera Selatan - Mustika Diana; Santi Dewiki; Miftahunnisa’ Igiriza (Institut Agama Islam Negeri Salatiga, 2020)
This study is entitled an analysis of library accessibility for disabled people based on the IFLA standard at the South Sumatra Province Library Office. This study aims to analyze and describe the accessibility of libraries for the disabled based on IFLA standards in the South Sumatra Library Office. This research is a type of qualitative descriptive research. Data collection methods used in this study were by interview, documentation and observation based on the IFLA standard checklist in the field. From the research that has been done, the results show that the suitability level of accessibility is 42 out of 102 items or 41.17%, while that which is not appropriate there are 60 items out of 102 items or 58%. it can be said that the accessibility of libraries for the disabled based on IFLA standards in the South Sumatra Province Library Service is not yet appropriate. From the situation in fulfilling the accessibility of disabilities in the library. The constraints that the results of this research South Sumatra Library have to face are the main ones in terms of funding. The available funds are inadequate to provide special facilities for people with disabilities, besides the constraints of human resources. Human resources do not yet have special competencies for the development of both collections and special infrastructure facilities for the disabled. Besides that, librarians do not yet have the special service competency of people with disabilities. In terms of collaboration, the library has difficulty finding suitable partners to establish cooperation in fulfilling services for the disabled. To increase the service for the disabled library should provide training to librarians in providing services for users with special needs or disabled